Analisis regresi data panel terhadap indeks pembangunan manusia (IPM) kabupaten/kota di Jawa Timur tahun 2017-2021 - Nikmah, Ifadhotun (Majalah Ilmiah Matematika dan Statistika, 2023)
The Human Development Index (HDI) is one of the main performance indicators that becomes a benchmark for the success of human development which consists of the dimensions of education, health and per capita expenditure. The government's role is very strategic in determining development priorities to realize an improved human development index. The purpose of this researchwas to determine the effect of the variables of Poverty Level, Economic Growth and GRDP per Capita on the Human Development Index (HDI) in 38 Regencies/Cities in East Java Province in 2017-2021. The technique used in this research is Panel Data Regression analysis. The result indicate that the Fixed Effect Model (FEM) Cross Section Weight was chosen as the best modelcompared to the Common Effect Model (CEM) and Random Effect Model (REM). Simultaneously, the poverty rate, economic growth and GRDP per capita have a significant effect on the HDI. Partially, poverty level and economic growth have a negative and significant impact on HDI in districts/cities in East Java, while income per capita has a positive and significant impact on HDI. Economic growth has a negative effect on HDI due to a contraction in economic growth to minus in 2021 due to the Covid-19 pandemic.The variable that has the most influence on the HDI is the poverty rate Keywords: HDI, panel data regression, fixed effect model cross section weightMSC2020: 62J05